Modeling of GTL-Power Coproduction as a means of optimisation of GTL plants - Ubanozie Julian Obibuike; Stanley Toochukwu Ekwueme; Nnaemeka Princewill Ohia; Onyejekwe Ifeanyi Michael (Zaštita Materijala)
Gas-to-Liquids (GTL) technologies have the potential to convert associated flare gases into premium transport liquids, creating a market for the otherwise stranded resource. However, the capital cost of GTL plants has over the years hampered the choice of the project. The drive for GTL is improved by optimization of the plant such that its efficiency and profitability is increased. One such notable improvement in GTL plant configuration is the integration of power production unit in the GTL process plant such that GTL liquids production and electricity production can occur concurrently in the same plant. This method generally called GTL-power co-production will increase the overall efficiency and profitability of existing GTL plant process and present ways to economically optimize the heat loss through the by-product streams (steam and flue gas streams). The utilization of the by-product streams will account for reductions in thermal inefficiencies within the GTL plant process. In this work, additional unit is added to the 863.3 m3 /d GTL product plant configuration to utilize the by-product steam stream for electricity generation. This additional electricity unit generated 10 MW of electricity increasing the net present value (NPV) of the plant by 4.72% while the net cash recovery (NCR) increased by 3.87%. Furthermore the pay-out time reduced by 2%. The GTL-Electricity co-production has proven to be a means of optimizing GTL plant, having capability to yield more profits due to reduced capital and operational expenses than if the plants were operated separately.